Molecular biological research on olfactory chemoreception in fishes - H. Hino; N. G. Miles; H. Bandoh; H. Ueda (Journal of Fish Biology, 2009)
This review describes recent molecular biological research on olfactory chemoreception in fishes. The recent rapid development of molecular biological techniques has provided new valuable information on the main and vomeronasal olfactory receptor (OR) genes, the axonal projection from ciliated, microvillous and crypt‐olfactory receptor cells to the olfactory bulb, properties of odorant substances and olfactory imprinting and homing in salmon. Many important questions, however, remain unanswered on functional differences among OR genes, on ligand binding to each OR and on the molecular biological mechanisms underlying olfactory imprinting and homing in salmon. Olfactory chemoreception is believed to be the oldest sensory cue for both animal survival and adaptation to various different environments. Further intensive molecular biological research on olfactory memory formation and remembrance should be carried out to clarify the fundamental process of olfactory chemoreception in fishes.